The Temperature Dependence of Predation Stress and Prey Nutritional Stoichiometry - Schmitz, Oswald J.; Rosenblatt, Adam E. (Frontiers in Ecology and Evolution, 2017)
Prey at risk of predation may experience stress and respond physiologically by altering their metabolic rates. Theory predicts that such physiological changes should alter prey nutrient demands from N-rich to C-rich macronutrients and shift the balance between maintenance and growth/reproduction. Theory further suggests that for ectotherms, temperature stands to exacerbate this stress. But, the behavior of many prey species facing perceived predation risk is the opposite of these predictions, consuming more N-rich resources. Here we revisit the original Threshold Elemental Ratio (TER) theoretical framework that inspired the idea of shifts in elemental (C:N) stoichiometry in response to chronic predation stress to reconcile the different prey responses. We examine the interactive effects of predation stress and temperature stress by exploring mathematically how the component physiological variables that determine TER vary individually with temperature. These functional relationships are then embedded into the equation for TER to predict how C and N intake should vary with and without predation stress across temperature gradients. This new theory reconciles the different prey responses and explains why and when species ought to consume more N vs more C when stressed by perceived predation, depending on the nature of their thermal performance with rising temperature. The theory also points to new ways to conduct experimental evaluations testing the temperature sensitivity of prey to predation stress.